Evidence of In Utero Transmission of Classical Scrapie in Sheep - Spiropoulos, John (American Society for Microbiology, 2014)
Classical scrapie is one of the transmissible spongiform encephalopathies (TSEs), a group of fatal infectious diseases that affect the central nervous system (CNS). Classical scrapie can transmit laterally from ewe to lamb perinatally or between adult animals. Here we report detection of infectivity in tissues of an unborn fetus, providing evidence that in utero transmission of classical scrapie is also possible.